Mycoflora and occurrence of aflatoxin in dried vegetables in Benin, Mali and Togo, West Africa - Hell, K.; Gnonlonfin, G.J.B.; Kodjogbe, G.; Lamboni, Y.; Abdourhamane, I.K. (Elsevier, 2009)
Fungal infection and aflatoxin contamination was evaluated on 180 samples of dried vegetables such as okra, hot chilli, tomato, melon seeds, onion and baobab leaves from Benin, Togo and Mali collected in September to October 2006. These products are dried to preserve them for lean periods and decrease their perishability. Fungal contamination was evaluated after plating on selective media with a total of 561 fungal isolates identified, ranging from 18 in tomato and 218 in baobab leaves. Baobab leaves, followed by hot chilli and okra showed high incidence of fungal contamination compared to the other dried vegetables, while shelled melon seeds, onion leaves and dried tomato had lower levels of fungal contamination. Species of Aspergillus were dominant on all marketed dried vegetables irrespective of country. Mycotoxin assessment by Reversed-Phase High Performance Liquid Chromatography showed that only okra and hot chilli were naturally contaminated with aflatoxin B(1) and aflatoxin B(2), at concentrations of 6.0 microg/kg on okra and 3.2 microg/kg on hot pepper. This is the first time that mycotoxigenic fungi and resultant toxins were found on dried vegetable products sampled from African markets. Previous reports have mostly highlighted the risk of mycotoxin exposure from staple crops in Africa, but such risks now need to be evaluated for other products such as dried vegetables.